Entrepreneur Resilience Strategies through Innovation Management Practices to Manage Impact and Recovery in the Face of Pandemic - Sudirman Sudirman; Sopiah Sopiah (International Journal Labs, 2022)
After being declared a pandemic, Covid-19 has made everyone change and change a different lifestyle than before. In accordance with a survey conducted by IIPI, it shows that after the Covid-19 pandemic, 95% of MSMEs had a significant impact from the pandemic, and 75% of them experienced a decline in income. Socialization and counseling are carried out for MSME actors as preparation for facing the new norm. This is done so that MSME actors can survive and compete during the Covid-19 pandemic. This is also carried out as a form of effort from various parties in an effort so that MSME actors can increase productivity. Other methods used include material sharing, socialization, counseling, and also question and answer.